PENGARUH PENGAWASAN, DISIPLIN KERJA DAN KOMUNIKASI TERHADAP KINERJA PEGAWAI KANTOR CAMAT UJUNG BATU KABUPATEN ROKAN HULU TAHUN 2022 - Vioni Priyanto; M. Y. Tiyas Tinov (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2023)
The purpose of this study was to determine the effect of supervision, work discipline and communication on the performance of employees of the Ujung Batu sub-district office, Rokan Hulu Regency, either partially (alone) or simultaneously (together). This type of research is survey research using a quantitative approach, which in data collection the author collects information from 34 respondents using a questionnaire as the main method. Determination of the research sample with saturated sampling technique. Saturated Sampling is a sampling technique when all members of the population are used as samples, so that the data obtained is general in nature. Multiple Regression Analysis, Partial Test (t test), Simultaneous (F test) are data analysis techniques in this study using the IBM SPSS Statistics 25 application. The results show that (1) Partially the Supervision variable (X1) has a significant effect on Employee Performance (Y) in the Ujung Batu Sub-District Office, (2) Partially the variable of Work Discipline (X2) has a significant effect on Employee Performance (Y) in the Ujung Batu Sub-District Office, (3) Partially the Communication variable (X3) has no effect significantly on Employee Performance (Y) in the Ujung Batu Sub-District Office, and (4) Simultaneously the variables of Supervision (X1), Work Discipline (X2) and Communication (X3) have an influence on Employee Performance (Y) in the Ujung Batu Sub-District Office. Keywords: Supervision, Work Discipline, Communication, Employee Performance.